Impacts of Peer Collaboration, Teacher Feedback, and STEM Career Exposure on Girls’ Attitudes Toward Science and Mathematics in Lagos State, Nigeria - Adeniyi, Comfort Olawumi; Bamgbade, Elizabeth O.; Okafor, Judith Adaobi (NIU Journal of Social Sciences, 2025)
The study examined impacts of Peer Collaboration, Teacher Feedback, and STEM Career Exposure on Girls’ Attitudes Toward Science and Mathematics in Lagos State, Nigeria. The population for this study was made up of the all teachers and students in Education District V, Lagos State. The two instruments employed for data collection were a 4-point Likert scale questionnaire and teacher interview guide with a reliability value of 0.79 and 0.82 respectively. The data were analysed using Means and Standard deviation z-scores and P-values . The findings revealed that peer collaboration, teacher feedback, and STEM career exposure play pivotal roles in shaping girls’ attitudes towards STEM subjects. The study recommended among other schools and policymakers should integrate structured peer learning programs, mentorship programs, and career exposure activities into the curriculum to ensure continuous engagement in STEM fields. Also, schools should provide regular teacher training programs to improve the effectiveness of feedback strategies and implement structured feedback mechanisms to provide timely and constructive support to foster girls’ interest in STEM. Keywords:   Peer collaboration, teacher feedback, career exposure, learner engagement, attitude